La percezione della diversitá linguistica in Omero - Luna, Maria Elena de (Gerión. Revista de Historia Antigua, 2003)
The work intend to investigue the presence in the Homerics work of the knowledge of alloqlossia trough the analysis of some terms and periphrasis which define the linguistic diversity of the mentioned characters and people. A substantial plan of the anide is devoted to the interpretation of the expression Kares borbarophonoi in the Iliad II 867